Repurchase Intention in Digital Transportation Services: Storytelling and Emotional Attachment - Rahel Syalomitha Amabel; Siska Ernawati Fatimah (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study examines the effects of storytelling and emotional attachment on users’ intention to reuse Gojek services in Cirebon, using a quantitative approach with 240 respondents selected through purposive sampling. Design/methodology/approach: The study uses Partial Least Squares–based Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0 to analyze data. Findings: Both storytelling and emotional attachment influence the intention to reuse the service, with emotional attachment being the strongest factor. Storytelling increases user interest by engaging them through narratives. Research limitations/implications: The study is limited to Gojek users in Cirebon, and future research should consider other platforms and regions for broader insights. Practical implications: The findings suggest that storytelling and emotional attachment are key strategies for enhancing user loyalty and encouraging repeat usage of digital services. Originality/value: This study provides valuable insights into the role of emotional attachment and storytelling in increasing repurchase intention. Paper type: Research paper